Neutrality and Narratives: Situating Middle Grades Preservice Teachers in Broader Educational Discourses - Rachel Ranschaert (Middle Grades Review, 2021)
This paper forwards discourse analysis as a productive way to consider the ways in which the possibilities available for middle grades preservice teachers in justice-oriented teacher education programs are complicated by larger discourses relating to teacher neutrality and teacher education as a transformational narrative. To illustrate this, written journals from twelve preservice teachers in a justice-oriented teacher education program are analyzed and discussed.
Keywords: teacher education; social justice; middle grades; middle school